IMAGE AND IDENTITY OF MALAY ROYAL TOWN IN MALAYSIA - Ismail, Puteri Sharina; Adam, Mastura (PLANNING MALAYSIA, 2020)
The Malay Royal towns in Malaysia are typically the location for the royal administrative district. The history for these royal town’s ties back to the Malay Royal Institution. Unfortunately, some towns are slowly threatened. Therefore, this paper aims to investigate the town’s unique character that shapes its image and identity intending to identify the attributes and how the people perceived them. The study adopts the case study research approach with the use of multiple sources of evidence which involved the convenience sampling method of the local people in the Royal Town of Kuala Kangsar, and Pekan. The finding shows that the royal town’s preservation should include both tangible and intangible characters such as historical buildings, historical stories, and cultural events to support the identity of the place.